Words high-frequency drying processes simulation of wooden tangent towers in a vacuum chamber - A. N. Kachanov; D. A. Korenkov; A. A. Revkov; V. V. Maksimov; O. V. Vorkunov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. The service life duration of wooden tangent towers used on overhead transmission lines with a voltage of up to 35 kV depends on the quality of lumber drying and subsequent impregnation. The drying of tangent tower workpieces is currently carried out by atmospheric or convective methods and is the longest and one of the energy-consuming stages of their production. At the same time, there are promising electrotechnological drying installations that can reduce the duration and improve drying quality at comparable specific energy costs. Such installations include vacuum high-frequency complexes, the wide introduction of which is complicated by a number of unresolved scientific and technical problems like optimizing vacuum high-frequency drying modes and ensuring electromagnetic field uniformity in long workpieces. The purpose of this article is to obtain mathematical tools that simultaneously describe the cross-effects of electromagnetic phenomena and heat and mass transfer processes in long-sized lumber and contribute to the further solution of these problems. METHODS. The positions of the theory of electromagnetic field, heat mass transfer and heat mass exchange, methods of mathematical modeling were used for this purpose. Also the results of previous studies of electromagnetic field distribution in the cross-section and longitudinal sections of the working chamber loading are taken into account. RESULTS. А one-dimensional mathematical model is obtained. It describes the influence of electromagnetic wave distribution along the length of tangent towers and external medium parameters on the temperature and moisture content in the material. This model is characterized by the possibility of using simple algorithms for analyzing differential equation systems based on the finite differe nce method and requiring less initial data on the drying material properties. CONCLUSION. The obtained by using the proposed model and the method of its analysis the numerical study results are compared with the available experimental data. Based on this comparison it is concluded that the obtained model is adequate and more effective relative to other existing models of vacuum high-frequency drying. Generally, further use of the presented mathematical toolkit to optimize the design and modes of vacuum-high-frequency complexes in the task of drying wooden tangent towers will increase the reliability of overhead transmission lines.